Self-sealing behavior of compacted bentonite–sand mixtures containing technological voids. (March 2021) - Watanabe, Yasutaka; Yokoyama, Shingo
Abstract: The self-sealing behaviors of compacted Na- and Ca-bentonite–sand mixtures were investigated by conducting swelling–permeability tests with specimens containing three types of technological voids. The technological voids, including an upper gap, a surrounding gap, and a center hole of the specimens at 0.03–17.65% of the total cell volume, were sealed by the swelling of the specimen. The vertical and lateral pressures became steady during the experiments, resulting in equal equilibrium pressure in the surrounding gap. The unequal equilibrium pressure in the vertical and lateral directions was measured when the upper gap and center hole were set. The lateral pressure tended to be higher than the vertical pressure. The residual compaction pressure likely explains the higher equilibrium lateral pressure. The coefficient of permeability depended on the average effective montmorillonite dry density in both Na- and Ca-bentonite–sand mixtures. This study proposed an effective Na-montmorillonite dry density, focusing on the high swelling potential of montmorillonite with exchangeable Na ions. The effective Na-montmorillonite dry density of the specimen, including the swollen part, exhibited a unique relation with the permeability after self-sealing, despite the different ionic types of bentonite. Under fully saturated condition, the distribution of water content throughout the specimen after self-sealing suggested that the dry density of the swollen part was lower than the initial specimen part, despite the presence of steady state pressures. It is most likely that the density distribution remained after self-sealing if external factors, including changeable boundary conditions and pore water chemistry, are not considered. Although the specimen after self-sealing exhibited the potential for heterogeneous density, its permeability was approximately evaluated by using the average effective Na-montmorillonite dry density. Highlights: Self-sealing ability of compacted bentonite–sand mixtures. Swelling pressure after sealing the technological voids. Permeability after sealing the technological voids. Distribution of water content indicated heterogeneous density at physical balance.